2019
DOI: 10.9734/ajaees/2019/v35i130215
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Adoption Rate of Rice Production Technologies Introduced by Agricultural Research Outreach Centres (AROCs) by Farmers in Niger State, Nigeria

Abstract: The study assessed the determinants of adoption rate of rice production technologies introduced by Agricultural Research Outreach Centres in Nigeria. Data were collected using a multi-sampling technique. Data were analysed using simple descriptive statistics and multiple linear regression. Results revealed that respondents’ mean age was 50 years; level of formal education of farmers was low and farm size was 2.5ha on the average. Age, farming experience, years of schooling and number of extension visits were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 9 publications
4
8
0
Order By: Relevance
“…According to Ayedun and Adeniyi (2019), rice production is a profitable enterprise going by the high demand of rice grains in the market. Similar findings by Yusuf et al (2019) revealed that the current annual income from rice production in Niger State is as a result of adoption of improved rice farming practices introduced by Agricultural Research Outreach Centres (AROCs).…”
Section: Methodsmentioning
confidence: 58%
See 2 more Smart Citations
“…According to Ayedun and Adeniyi (2019), rice production is a profitable enterprise going by the high demand of rice grains in the market. Similar findings by Yusuf et al (2019) revealed that the current annual income from rice production in Niger State is as a result of adoption of improved rice farming practices introduced by Agricultural Research Outreach Centres (AROCs).…”
Section: Methodsmentioning
confidence: 58%
“…This is a pointer to the fact that rice farming practices in Niger State is better than that of Ogun State. Previous findings by Ojo and Ogunyemi (2013) and Yusuf, Salau and Girei (2019) showed that access and adoption of improved agronomic practices resulted in increased farm output. Table 2 show that 63.2% harvested more than 1.5tonnes/ha while 26.2% harvested 1.0 -4.0tonnes/ha.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…The level of education is a proxy of human capital. According to the literature, the educational level is an important determinant in the adoption of new agricultural technology [45,46]. Farmers with a higher education level may understand the necessity of adopting agricultural innovations.…”
Section: Variables and Empirical Hypothesesmentioning
confidence: 99%
“…Experienced rice farmers may be aware of the importance of agricultural innovations; therefore, they could respect the technology recommendations [47,48,50]. However, experience is often correlated with rice farmer's age; more experienced farmers might well be more risk-averse and less prone to face a change [43,46]. Experienced farmers may also have a good reputation with credit lenders [51].…”
Section: Variables and Empirical Hypothesesmentioning
confidence: 99%